Synthesis, Spectral Study and Biological Activity of Some Metal Ions Complexes with Bidentate Ligands - Bakir, Shaimaa Rhajab (Al-Nahrain Journal of Science, 2012)
A new neutral bidentate schiff base mixed ligand metal ions complexes of the composition, [ML1L] (NO3)2 where M=Co(II), Ni(II), Cu(II), Zn(II) and Cd (II) L1=(4-nitro benzylidene)-urea amine, L=La,Lb ligands derived from thiosemicarbazone and 4-chlorobenzaldehyde or 4-bromobenzaldehyde were synthesis and characterized by elemental analysis, magnetic susceptibility, molar conductivity, FT-IR, UV-Vis, and 1HNMR spectral studies .The conductivity measurements of cobalt(II), nickel (II),and copper (II) complexes were suggested to have a tetrahedral geometry, but Zn(II) and Cd (II) complexes were suggested to has square planner. The structural geometries of compounds were also suggested in gas phase by theoretical treatments, using Hyper chem-6 program for the molecular mechanics and semi-empirical calculations, an addition heat of formation (ΔHf ◦) and binding energy (ΔEb) for the free ligands and it’s metal complexes were calculated by using PM3 method .PM3 was used to evaluate the vibration spectra of Schiff bases and compare the theoretically calculated wave numbers with experimental values ,the theoretically obtained frequencies agreed calculation helped to assign unambiguously the most diagnostic bands. The antimicrobial activities of the metal chelats against the bacteria, Escherichia coli and Staphylococcus aureus were studied.